Handbook of radioactivity analysis - L'Annunziata, Michael F. (Academic Press, 2003)
The book describes the preparation of samples from a wide variety of matrices, assists the investigator or technician in the selection and use of appropriate radiation detector, and presents the latest state-of-the-art computerized and automated methods of analysis. Fundamentals of radioactivity properties, radionuclide decay, calculations involved, and methods of detection provide the basis for a thorough understanding of the analytical procedures. Therefore, the new Handbook of Radioactivity Analysis is also suitable as a teaching text for university and professional training courses. Key Features: & bull; New much expanded and updated edition with three additional chapters & bull; Provides modern procedures and guidelines for the analysis of natural and man-made environmental radionuclides & bull; Includes up-to-date detailed sample preparation techniques for soil, air, plant, water, biological tissue, filter material, gels, and surface swipes, etc. & bull; Describes much practical information for radioactivity monitoring, spectrometric analysis, and radiation dosimetry & bull; Covers state-of-the-art high sample throughput microplate analysis techniques and multi-detector scintillation proximity analysis & bull; Presents the latest methods of rapid electronic radionuclide imaging & bull; Written by twenty-five experts from eight countries & bull; Over 2,000 cited works from the journal references Why This Title? This updated and much expanded Second Edition is a proven authoritative handbook providing the reader with the principles, practical techniques, and procedures for the accurate measurement of radioactivity from the very low levels encountered in the environment to higher levels measured in radioisotope research, clinical laboratories, biological sciences, radionuclide standardization, nuclear medicine, nuclear power, fuel cycle facilities, and the implementation of nuclear safeguards. New, expanded and updated edition with three additional chapters Provides modern procedures and guidelines for the analysis of natural and man-made environmental radionuclides Includes up-to-date detailed sample preparation techniques for soil, air, plant, water, biological tissue, filter material, gels, surface swipes, etc. Provides practical information for radioactivity monitoring, spectrometric analysis, and radiation dosimetry Covers state-of-the-art high sample throughput microplate analysis techniques and multi-detector scintillation proximity analysis Presents the latest methods of rapid electronic radionuclide imaging Written by twenty-five experts from eight countries. Over 2,000 literature references.